Recognizing handshapes using small datasets - Cornejo Fandos, U.; Ríos, Gastón Gustavo; Ronchetti, Franco; Quiroga, Facundo Manuel; Hasperué, Waldo; Lanzarini, Laura Cristina (2019)
Advances in convolutional neural networks have made possible significant improvements in the state-of-the-art in image classification. However, their success on a particular field rests on the possibility of obtaining labeled data to train networks. Handshape recognition from images, an important subtask of both gesture and sign language recognition, suffers from such a lack of data. Furthermore, hands are highly deformable objects and therefore handshape classification models require larger datasets. We analyze both state of the art models for image classification, as well as data augmentation schemes and specific models to tackle problems with small datasets. In particular, we perform experiments with Wide- DenseNet, a state of the art convolutional architecture and Prototypical Networks, a state of the art few-shot learning meta model. In both cases, we also quantify the impact of data augmentation on accuracy. Our results show that on small and simple data sets such as CIARP, all models and variations of achieve perfect accuracy, and therefore the utility of the data is highly doubtful, despite its having 6000 samples. On the other hand, in small but complex datasets such as LSA16 (800 samples), specialized methods such as Prototypical Networks do have an advantage over other methods. On RWTH, another complex and small dataset with close to 4000 samples, a traditional and state-of-the-art method such as Wide-DenseNet surpasses all other models. Also, data augmentation consistently increases accuracy for Wide-DenseNet, but not fo Prototypical Networks.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Congreso Argentino de Ciencias de la Computación (25to : 2019 : Río Cuarto, Córdoba)
Keywords: REDES NEURONALES; lenguaje de señas